Optimal design of a heat exchanger network composed of parallel tubes - Miguel, A. F. (2012)
Networks of tubes for heat and mass transport abound both in nature and in engineered systems. In this paper we study the optimal design of heat exchanging flow networks composed of parallel tubes. The impact of the network size-limiting constrains (surface area, tubes diameter), fluid flow regime, as well as the fluid pumping power requirements is addressed in this paper for the cases when Biot number is smaller than 0.1.